2021
DOI: 10.1007/s11414-021-09761-5
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Outcomes Associated with COVID-19 Pandemic in a Group of Health Care Professionals

Abstract: Analysis of health care workers’ stress levels during the COVID-19 virus pandemic, and whether there is a relationship between health care workers’ stress levels and mental health in the context of coping with stress. One hundred and seventy professionally active health care workers took part in the study: doctors (n=41), nurses (n=114) and paramedics (n = 15). On average, study subjects were 37 years old and had 14 years of work experience. The following were used in this questionnaire-based study: General He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…All participants agreed to voluntarily participate in the study by signing an informed consent. They were asked to fill in the survey consisting of two parts: the first part included a respondent's particulars (age, sex, year of study) and ten close-ended questions concerning the symptoms of SSDs and pain (Likert scale) [39][40][41][42][43][44][45]. The second part consisted of standardized psychological questionnaires, PSS10 (perceived stress scale), Mini-Cope (Inventory for measuring coping with stress), DS14 (Type-D scale) [46][47][48][49][50][51][52][53][54].…”
Section: Methodsmentioning
confidence: 99%
“…All participants agreed to voluntarily participate in the study by signing an informed consent. They were asked to fill in the survey consisting of two parts: the first part included a respondent's particulars (age, sex, year of study) and ten close-ended questions concerning the symptoms of SSDs and pain (Likert scale) [39][40][41][42][43][44][45]. The second part consisted of standardized psychological questionnaires, PSS10 (perceived stress scale), Mini-Cope (Inventory for measuring coping with stress), DS14 (Type-D scale) [46][47][48][49][50][51][52][53][54].…”
Section: Methodsmentioning
confidence: 99%
“…Ziarko et al [ 29 ] assessed the level of stress among doctors (n = 41), nurses (n = 114) and paramedics (n = 15) during the COVID-19 pandemic and analysed whether there was a relationship between the stress level and mental health of healthcare workers in the context of coping with stress. Among medical workers, nurses experienced the most severe stress.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid research world‐wide has reported on the unprecedented COVID‐19‐related challenges facing health and social care workers (HSCWs) and how these prompted substantial rates of mental health deterioration (Badahdah et al, 2020 ; Barzilay et al, 2020 ; Cag et al, 2021 ; Cogan et al, 2022 ; De Kock et al, 2021 ; Fang et al, 2021 ; Feinstein et al, 2020 ; Mascayano, et al, 2022 ; Mehta et al, 2021 ; Moitra et al, 2021 ; Odani et al, 2022 ; Rana et al, 2020 ; Vanhaecht et al, 2021 ; Young et al, 2021 ; Ziarko et al, 2022 ). Work published during the first wave of COVID‐19 largely focused on healthcare workers, reporting clinically significant symptoms of stress, depression, anxiety, insomnia, burnout and psychological distress (García‐Fernández et al, 2020 ; Inchausti et al, 2020 ; Nyashanu et al, 2022 ) and emphasised the importance of safeguarding staff mental health (De Brier et al, 2020 ; Jordan et al, 2021 ; Lake et al, 2022 ; Nyashanu et al, 2022 ; Spoorthy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%